On the challenges of embedding assessments of self-regulated learning into licensure activities in health professions education - Neufeld, Adam (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
How can we claim that we are creating “lifelong learners” if we are not embedding assessments of self-regulated learning (SRL) into health professions education (HPE)? A good question but one that we must not try to answer too hastily. Some may consider SRL to be such an important competency that failing to assess it disservices everyone involved in HPE, including patients. I would argue that assessment of SRL may well be justified, but that how it is measured, what we might find, and what the implications of those findings might be, are equally critical to consider. The fact is that learners in HPE face many pressures that influence not just the quantity but also the quality of their self-regulation towards learning, which measures of SRL would have to account for, to be effective. Drawing on the self-regulation literature and self-determination theory (SDT) in particular, my aim in the present commentary is to discuss some of the nuances and issues that we would need to address, if we were to move towards a unified approach to assessing SRL in HPE.